Новые виды земляных блошек (Coleoptera, Chrysomelidae, Halticinae) из Средней Азии. Сообщение II - Палий, В.Ф. (Вестник зоологии, 1968)
The fauna of Coleoptera, Chrysomelidae, Halticinae was investigated for 6 years (1961-1966) on the territory of the Central Asia republics and South Kazakhstan. Among the thousands of individuals of genus Haltica the following species are found out and described: H. alaiensis Palij, sp. n. from Alai; H. susamyrica Palij, sp. n. from the high valleys of the central Tien Shan; H. lopatini Palij., sp. n. from the Ferghana valley; H. alchymillae Palij, sp. n. from the high ridges of the east Tien Shan (within the boundaries of the USSR).